The Blue Carbon Cost Tool – understanding market potential and investment requirements for high-quality coastal wetland projects - Stefanie Simpson; Lindsey S. Smart; Emily Landis; Stephanie Van Laere; Abu S. M. G. Kibria; Olga Albot; Mark Beeston; Catherine E. Lovelock; Robert I. McDonald; Ryan P. Moyer; Thomas A. Worthington; Tania L. Maxwell; et al. (Frontiers in Marine Science, 2025)
Blue carbon ecosystems, such as mangroves, tidal marshes, and seagrasses, are important for climate mitigation. As carbon sinks, they often exhibit higher per hectare carbon storage capacity and sequestration rates than terrestrial systems. These ecosystems provide additional benefits, including enhancing water quality, sustaining biodiversity, and maintaining coastal resilience to climate change impacts. The widespread loss of blue carbon ecosystems due to anthropogenic activities can contribute to increasing carbon emissions globally. Monetizing blue carbon through carbon credits offers an avenue to generate revenue and incentivize conservation and restoration efforts. However, limited data on project costs and carbon benefits make prioritization of blue carbon projects challenging. To address these challenges, we have developed, in collaboration with blue carbon experts, the Blue Carbon Cost Tool. This is a user-friendly interface enabling comparison of three core market project components – 1) carbon credit estimation, 2) project cost estimation, and 3) a qualitative, non-economic feasibility assessment – to assess and compare potential for blue carbon projects. Tool simulations with data available from nine countries demonstrate (a) how factors such as country, ecosystem type and project scale drive variability, (b) the need for local or project-specific data to enhance accuracy and reduce uncertainty, particularly in tidal marsh and seagrass systems, and (c) that higher price tolerance or upfront capital is needed to bridge implementation and maintenance cost gaps. The Blue Carbon Cost Tool can aid project developers and investors to better understand market opportunity and the resources needed to develop high quality blue carbon market projects.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Process Monitoring of Moisture Content and Mass Transfer Rate in a Fluidised Bed with a Low Cost Inline MEMS NIR Sensor - Claudio R. Avila; Joan Ferré; Rodrigo Rocha de Oliveira; Anna de Juan; Wayne E. Sinclair; Faiz M. Mahdi; Ali Hassanpour; Timothy N. Hunter; Richard A. Bourne; Frans L. Muller (Pharmaceutical Research, 2020)
Purpose The current trend for continuous drug product manufacturing requires new, affordable process analytical techniques (PAT) to ensure control of processing. This work evaluates whether property models based on spectral data from recent Fabry–Pérot Interferometer based NIR sensors can generate a high-resolution moisture signal suitable for process control. Methods Spectral data and offline moisture content were recorded for 14 fluid bed dryer batches of pharmaceutical granules. A PLS moisture model was constructed resulting in a high resolution moisture signal, used to demonstrate (i) endpoint determination and (ii) evaluation of mass transfer performance. Results The sensors appear robust with respect to vibration and ambient temperature changes, and the accuracy of water content predictions (±13 % ) is similar to those reported for high specification NIR sensors. Fusion of temperature and moisture content signal allowed monitoring of water transport rates in the fluidised bed and highlighted the importance water transport within the solid phase at low moisture levels. The NIR data was also successfully used with PCA-based MSPC models for endpoint detection. Conclusions The spectral quality of the small form factor NIR sensor and its robustness is clearly sufficient for the construction and application of PLS models as well as PCA-based MSPC moisture models. The resulting high resolution moisture content signal was successfully used for endpoint detection and monitoring the mass transfer rate.

Phylogeographical patterns and a cryptic species provide new insights into Western Indian Ocean giant clams phylogenetic relationships and colonization history - Cécile Fauvelot; Dario Zuccon; Philippe Borsa; Daphné Grulois; Hélène Magalon; Florentine Riquet; Serge Andréfouët; Michael L. Berumen; Tane H. Sinclair‐Taylor; Pauline Gélin; Faustinato Behivoke; Jan Johan ter Poorten; et al. (Journal of Biogeography, 2020)
Aim The unique biodiversity in the Red Sea is the result of complex ecological and evolutionary processes driven by Pleistocene climatic change. Here we investigate the species diversity, phylogenetic relationships and phylogeographical patterns of giant clams in the Western Indian Ocean (WIO) and the Red Sea to explore scenarios of marine speciation in this under‐studied region. Location Mozambique Channel, Madagascar, and the Mascarene Islands (WIO); the Farasan Islands (Red Sea). Taxon Giant clams of the genus Tridacna (Cardiidae: Tridacninae). Methods Giant clams were sampled as complete organisms or through underwater biopsies. Nuclear ( 28S ) and mitochondrial ( 16S and COI ) DNA sequences were subjected to Bayesian and maximum likelihood analyses to generate a phylogenetic hypothesis for all known species within the genus Tridacna . Bayesian inference with molecular and fossil calibration was used to infer their colonization history. Results From the 10 genetically distinct clades recovered from the analyses of 253 sequenced specimens, five distinct Tridacna lineages were sampled, three of which were endemics of the WIO and the Red Sea. Each lineage corresponded to a distinct species, except one grouping the two formerly known WIO endemics, T. lorenzi and T. rosewateri . This lineage clustered with two other well‐supported lineages: the Red Sea endemic T. squamosina , and a previously unrecognized lineage, restricted to the WIO, for which we resurrect the long‐forgotten name T. elongatissima Bianconi, 1856. For the two other species sampled ( T. maxima and T. squamosa ), contrasting phylogeographical patterns were observed. Main conclusions Our data confirm the validity of the species T. rosewateri , a WIO endemic genetically indistinguishable from T. lorenzi , which should be considered a junior synonym. The phylogenetic placement of the newly resurrected T. elongatissima provides insights into the probable origin of T. squamosina , which split from its sister species no later than 2 Ma, likely during Middle Pleistocene glacial periods. Two scenarios are discussed. Our results also suggest that T. maxima invaded the Red Sea more recently and that contemporary gene flow between Red Sea and WIO T. maxima is highly restricted. The deep Red Sea partition observed in T. squamosa suggests a much older divergence and raises the question of a possible cryptic lineage.

A framework for predicting which non-native individuals and species will enter, survive, and exit human-mediated transport - James S. Sinclair; Julie L. Lockwood; Sarah Hasnain; Phillip Cassey; Shelley E. Arnott (Biological Invasions, 2020)

Long‐term monitoring of Serengeti bird species occurrence, abundance, and habitat - L. Francisco Henao-Diaz; Anthony R. E. Sinclair (Ecology, 2020)
The Serengeti ecosystem contains one of the most diverse bird assemblages in Africa. We present here a data set consisting of abundances of bird species in different habitats of the Serengeti ecosystem over a 87‐yr time frame. This data set comprises 66,643 georeferenced occurrences for 568 species from 1929 to 2017. Most records contain feeding location, food source, distribution status, and observation locality. The records originate from three different but complementary methodologies: points, sites, and transects. The point method (bird species records 1929–2017) is based on ad hoc observations and includes rare species or those in special habitats. These points came from published records as well from the research program of A. R. E. Sinclair and colleagues. The site method (1966–2017) is based on structured observations at sites selected to represent specific habitats, and replicated within habitats and over time. At each site, birds were recorded by sight and sound over a radius of 50 m for 10 min. The transect method (1997–2011) is based on road transects covering different areas of the ecosystem. Road transects were traversed using a vehicle with observers travelling at 30 km/h. Bird species were those easily seen from a vehicle out to 50 m either side. As most transects were traversed multiple times, this method provides information on temporal change in abundance for a select set of species. No copyright restrictions apply to the use of this data set other than citing this publication.

Enhancing maize productivity in agroforestry systems through managing competition: lessons from smallholders’ farms, Rift valley, Kenya - J. Nyaga; C. W. Muthuri; E. Barrios; I. Öborn; F. L. Sinclair (Agroforestry Systems, 2019)

Cranial morphological scaling and relative prey size limitations for a native predator in an invaded system - Eliza I. Gilbert; Scott L. Durst; Angela P. James; Jason E. Davis; Thomas B. Sinclair; Nathan R. Franssen (Environmental Biology of Fishes, 2018)

The limitations of some European healthcare databases for monitoring the effectiveness of pregnancy prevention programmes as risk minimisation measures - R. A. Charlton; V. Bettoli; H. J. Bos; A. Engeland; E. Garne; R. Gini; A. V. Hansen; L. T. W. de Jong-van den berg; S. Jordan; K. Klungsøyr; A. J. Neville; A. Pierini; et al. (European Journal of Clinical Pharmacology, 2018)

Can we predict ectotherm responses to climate change using thermal performance curves and body temperatures? - Brent J. Sinclair; Katie E. Marshall; Mary A. Sewell; Danielle L. Levesque; Christopher S. Willett; Stine Slotsbo; Yunwei Dong; Christopher D. G. Harley; David J. Marshall; Brian S. Helmuth; Raymond B. Huey (Ecology Letters, 2016)
Thermal performance curves ( TPC s), which quantify how an ectotherm's body temperature ( T b ) affects its performance or fitness, are often used in an attempt to predict organismal responses to climate change. Here, we examine the key – but often biologically unreasonable – assumptions underlying this approach; for example, that physiology and thermal regimes are invariant over ontogeny, space and time, and also that TPC s are independent of previously experienced T b. We show how a critical consideration of these assumptions can lead to biologically useful hypotheses and experimental designs. For example, rather than assuming that TPC s are fixed during ontogeny, one can measure TPC s for each major life stage and incorporate these into stage‐specific ecological models to reveal the life stage most likely to be vulnerable to climate change. Our overall goal is to explicitly examine the assumptions underlying the integration of TPC s with T b , to develop a framework within which empiricists can place their work within these limitations, and to facilitate the application of thermal physiology to understanding the biological implications of climate change.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Farmers in Côte d’Ivoire value integrating tree diversity in cocoa for the provision of ecosystem services - E. Smith Dumont; G. M. Gnahoua; L. Ohouo; F. L. Sinclair; P. Vaast (Agroforestry Systems, 2014)

Is increased juvenile infection the key to recovery of wild rabbit populations from the impact of rabbit haemorrhagic disease? - G. J. Mutze; R. G. Sinclair; D. E. Peacock; L. Capucci; J. Kovaliski (European Journal of Wildlife Research, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Mapping of quantitative trait loci for canopy-wilting trait in soybean (Glycine max L. Merr) - Hussein Abdel-Haleem; Thomas E. Carter; Larry C. Purcell; C. Andy King; Landon L. Ries; Pengyin Chen; William Schapaugh; Thomas R. Sinclair; H. Roger Boerma (Theoretical and Applied Genetics, 2012)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Synoptic Controls on Boundary-Layer Characteristics - Victoria A. Sinclair; Stephen E. Belcher; Suzanne L. Gray (Boundary-Layer Meteorology, 2010)

Characterisation of polymorphic microsatellite markers in the widespread Australian seagrass, Posidonia australis Hook. f. (Posidoniaceae), with cross-amplification in the sympatric P. sinuosa - E. A. Sinclair; J. Anthony; G. T. Coupland; M. Waycott; M. D. Barrett; R. L. Barrett; M. L. Cambridge; M. J. Wallace; K. W. Dixon; S. L. Krauss; G. A. Kendrick (Conservation Genetics Resources, 2009)

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Sensitivity of Systematic Reserve Selection to Decisions about Scale, Biological Data, and Targets: Case Study from Southern British Columbia - LEANNA D. WARMAN; A. R. E. SINCLAIR; G. G. E. SCUDDER; BRIAN KLINKENBERG; ROBERT L. PRESSEY (Conservation Biology, 2004)
The identification of conservation areas based on systematic reserve‐selection algorithms requires decisions related to both spatial and ecological scale. These decisions may affect the distribution and number of sites considered priorities for conservation within a region. We explored the sensitivity of systematic reserve selection by altering values of three essential variables. We used a 1:20,000–scale terrestrial ecosystem map and habitat suitability data for 29 threatened vertebrate species in the Okanagan region of British Columbia, Canada. To these data we applied a reserve‐selection algorithm to select conservation sites while altering selection unit size and shape, features of biodiversity (i.e., vertebrate species), and area conservation targets for each biodiversity feature. The spatial similarity, or percentage overlap, of selected sets of conservation sites identified (1) with different selection units was ≤40%, (2) with different biodiversity features was 59%, and (3) with different conservation targets was ≥94%. Because any selected set of sites is only one of many possible sets, we also compared the conservation value (irreplaceability) of all sites in the region for each variation of the data. The correlations of irreplaceability were weak for different selection units (0.23 ≤r≤ 0.67), strong for different biodiversity features (r= 0.84), and mixed for different conservation targets (r= 0.16; 0.16; 1.00). Because of the low congruence of selected sites and weak correlations of irreplaceability for different selection units, recommendations from studies that have been applied at only one spatial scale must be considered cautiously.

Species distributions, surrogacy, and important conservation regions in Canada - Leanna D. Warman; David M. Forsyth; A. R. E. Sinclair; Kathryn Freemark; Harold D. Moore; Thomas W. Barrett; R. L. Pressey; Denis White (Ecology Letters, 2004)
Conservation actions could be more efficient if there is congruence among taxa in the distribution of species. Patterns in the geographical distribution of five taxa were used to identify nationally important regions for conservation in Canada. Two measures of surrogacy were significantly and positively correlated among taxa, and conservation areas selected for one taxon represented other taxa significantly better than random selections. However, few large protected areas exist in the sites of highest conservation value in southern Canada; these regions are therefore a priority for future conservation regard. By focusing this effort on threatened and endangered species, which are a national priority in Canada, most other species could also benefit.

A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - R. A. Sharrock; F. L. Sinclair; C. Gliddon; I. M. Rao; E. Barrios; P. J. Mustonen; P. Smithson; D. L. Jones; D. L. Godbold (Mycorrhiza, 2004)

On-farm evaluation of the establishment of clonal rubber in multistrata agroforests in Jambi, Indonesia - S. E. Williams; M. van Noordwijk; E. Penot; J. R. Healey; F. L. Sinclair; G. Wibawa (Agroforestry Systems, 2001)

Productivity and profitability of multistrata organic versus conventional coffee farms in Costa Rica - A. E. Lyngbæk; R.G. Muschler; F. L. sinclair (Agroforestry Systems, 2001)

Growth variability in a Senegalese provenance of Acacia nilotica ssp. tomentosa - E. Wolde-Mieskel; F. L. Sinclair (Agroforestry Systems, 2000)

Cod and haddock spawning on Georges Bank in relation to water residence times - F. H. Page; M. Sinclair; C. E. Naimie; J. W. Loder; R. J. Losier; P. L. Berrien; R. G. Lough (Fisheries Oceanography, 1999)
The seasonal and geographical patterns of spawning for Georges Bank cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are estimated using composite distributions of stage I eggs derived from the Marine Resources Monitoring, Assessment and Prediction (MARMAP) data set (1977–1987). The inferred mean spawning locations are compared with patterns in particle residence times derived from a three‐dimensional prognostic circulation model that estimates the tidal and seasonal mean circulation. The comparisons indicate that cod and haddock spawning occurs at times and locations characterized by model residence times in excess of 35 d. The results are discussed in the context of fish population regulation theory, particularly the member/vagrant hypothesis and the concept of abundance‐dependent vagrancy.